2017
DOI: 10.5606/archrheumatol.2017.6075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Metabolic Factors of Hyperuricemia in an Elderly Agricultural and Fishing Population in Taiwan

Abstract: Objectives: This study aims to explore the potential condition-related sex differences to understand the overall pathogenesis of hyperuricemia among the elderly agricultural and fishing population in Taipei, Taiwan. Patients and methods: This study included 4,372 healthy elderly agricultural and fishing professionals (2,766 males, 1,606 females; mean age 74.4±6.6 years; range 65.0 to 90.3 years) voluntarily admitted to a teaching hospital in Taipei, Taiwan for physical exams in 2010. Their fasting blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…Based on the obtained data, we estimated the population prevalence of hyperuricemia at 23.1% among older adults, and 25.5% in women and 19.2% in men. This makes the Polish prevalence one of the highest in older populations reported worldwide [27,[38][39][40][41][42][43]. This is caused by the inclusion of a large percentage of octa-and nonagenarians, with a 1.48-times higher frequency of hyperuricemia in relation to younger seniors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained data, we estimated the population prevalence of hyperuricemia at 23.1% among older adults, and 25.5% in women and 19.2% in men. This makes the Polish prevalence one of the highest in older populations reported worldwide [27,[38][39][40][41][42][43]. This is caused by the inclusion of a large percentage of octa-and nonagenarians, with a 1.48-times higher frequency of hyperuricemia in relation to younger seniors.…”
Section: Discussionmentioning
confidence: 99%
“…and women over the age of 65, respectively [41,42]. The highest incidence of hyperurice mia was found in Ireland, reaching 27.7% in 60-80-year-olds and 43.0% in people over 8 years of age [43].…”
Section: Study Populationmentioning
confidence: 94%
“…In Indonesia according to the World Health Organization in 2013, the prevalence of hyperuricemia was 81% [4]. While a study in North Halmahera also showed that the prevalence of hyperuricemia was high, namely, 60% (men 50.83% and women 69.17%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan the prevalence of hyperuricemia is 30.4%, in men (30.2%), and women (30.6%). This prevalence will increase significantly with age [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hyperuricemia is increasing worldwide (Yu et al, 2017;Zhu et al, 2017). Elevated serum uric acid levels are associated with increment of mortality rate (Jung et al, 2018;Yu et al, 2017) and lifestyle-related disease such as chronic renal failure (Yamamoto et al, 2018;Chen et al, 2019;Lai et al, 2018;Yu et al, 2017;Zhang et al, 2018;Li et al, 2018), cardiovascular disease (Ozalp Kizilay et al, 2019;Jung et al, 2018;Okazaki et al, 2017;Yu et al, 2017;Zhang et al, 2018;Zhu et al, 2017;Yamamoto et al, 2018), hyperglycemia (Takir et al, 2015;Zhu et al, 2017;Wardhana and Rudijanto, 2018;Ozalp Kizilay et al, 2019), elevated glycated hemoglobin (HbA1c) (Wardhana and Rudijanto, 2018), insulin resistance (Ozalp Kizilay et al, 2019;Wardhana and Rudijanto, 2018), increased risk of diabetes mellitus (Kuwabara et al, 2017;Ozalp Kizilay et al, 2019;Wardhana and Rudijanto, 2018;Yu et al, 2017;Zhang et al, 2018;Zhu et al, 2017) and obesity (Zhu et al, 2017;Ali et al, 2018;Zhang et al, 2016). Recent studies revealed that maybe there is a bilateral association between hyperuricemia and obesity, and they influence each other based on multiple mechanisms (Ozalp Kizilay et al, 2019;Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%